Pay for Performance in Health Care : Methods and Approaches - Jerry Cromwell; Michael G. Trisolini; Gregory C. Pope; Janet B. Mitchell; Leslie M. Greenwald (RTI Press, 2011)
This book provides a balanced assessment of pay for performance (P4P), addressing both its promise and its shortcomings. P4P programs have become widespread in health care in just the past decade and have generated a great deal of enthusiasm in health policy circles and among legislators, despite limited evidence of their effectiveness. On a positive note, this movement has developed and tested many new types of health care payment systems and has stimulated much new thinking about how to improve quality of care and reduce the costs of health care. The current interest in P4P echoes earlier enthusiasms in health policy—such as those for capitation and managed care in the 1990s—that failed to live up to their early promise. The fate of P4P is not yet certain, but we can learn a number of lessons from experiences with P4P to date, and ways to improve the designs of P4P programs are becoming apparent. We anticipate that a “second generation” of P4P programs can now be developed that can have greater impact and be better integrated with other interventions to improve the quality of care and reduce costs.